IMPROVING CHILDREN'S COGNITIVE ABILITY THROUGH BLOCK EDUCATIONAL GAMES - Fifi Elvia; Evi Selva Nirwana; Erni Munastiwi (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
This research was carried out with the aim of providing knowledge or choices to parents and teachers or educators that cognitive development can be enhanced through playing educational games with blocks. This research is a qualitative descriptive research. With data collection techniques observation, interviews, and documentation. The research subjects were 20 students of class B TK Darussalam Plus Yogyakarta. The results showed that there was an increase in children's cognitive abilities through educational games in the form of blocks. This is evidenced by the increase in children's cognitive abilities with the application of educational games, such as being able to classify different according to type and color, compare shapes around them, understand various number concepts, distinguish between large and small, long and short, time, space, and able to make a good picture or design.